Employees assimilation and socialization tactics in organization - Kamaruddin, Kardina; Ali, Noor Malinjasari; Azizan, Nurul Nadzirah; Mohd Noor, Hasmida; Borhanuddin, Rahayu Izwani; Mokhlas, Hasmi (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2022)
Employees' assimilation or also widely mentioned in literature i as organizational assimilation, is a dynamic process that occurs between newcomersand members of an organization that includes the organization's attempt to orient and train newcomers, along with the recruits' effort to negotiate their roles in the organization (Gailliard, Myers & Seibold, 2010). Organizations usually design the cut-off for newcomer-member transition (assimilation) period between three to six months after recruitment of the newcomer.